Theoretical and experimental study on the angular dependence of scattering processes in X‐ray fluorescence systems. (23rd May 2013) - Guerra, M.; Manso, M.; Pessanha, S.; Longelin, S.; Carvalho, M. L.
Abstract : The role of X‐ray reflectivity, coherent, and incoherent scattering has been studied in light samples. The angular dependence of these processes was evaluated, and the best geometrical settings for X‐ray fluorescence spectrometers was studied both for symmetrical and asymmetrical setups. Emphasis is given to biaxial planar geometry rather than triaxial orthogonal geometry, due to the use of low power X‐ray tubes and non‐cryogenic detectors in portable instruments rather than desktop or larger laboratory instruments. The detection limits of the reference material Orchard leaves (NBS‐1571) were calculated for each studied geometry. The specular reflectivity at the sample plane, as well as the irradiated volume was found to be of paramount importance in the angular dependence of the coherent and incoherent peaks description. The best geometry for symmetrical spectrometers in the 1–30 keV energy range is in the 70°–90° interval due to the Compton and Rayleigh scatterings of the incident radiation. Copyright © 2013 John Wiley & Sons, Ltd.